Evaluating the most appropriate pooling ratio for EDTA blood samples to detect Bluetongue virus using real-time RT-PCR - Flannery, John (Vet Microbiol, 2018)
The control of Bluetongue virus (BTV) presents a significant challenge to European Union (EU) member states as trade restrictions are placed on animals imported from BTV-affected countries. BTV surveillance programs are costly to maintain, thus, pooling of EDTA blood samples is used to reduce costs and increase throughput. We investigated different pooling ratios (1:2, 1:5, 1:10 and 1:20) for EDTA blood samples to detect a single BTV positive animal. A published real-time RT-PCR assay (Hofmann et al., 2008) and a commercial assay (ThermoFisher VetMax™ BTV NS3 kit) were used to analyse BTV RNA extracted from pooled EDTA blood samples. The detection rate was low for the onset of infection sample (0–2 days post infection (dpi); C(T) 36) irrespective of the pooling ratio. Both assays could reliably detect a single BTV-positive animal at early viraemia (3–6 dpi; C(T) 33) when pooled, however, detection rate diminished with increasing pooling ratio. A statistical model indicated that pooling samples up to 1:20, is suitable to detect a single BTV positive animal at peak viraemia (7–12 dpi) or late infection (13–30 dpi) with a probability of detection of >80% and >94% using the Hofmann et al. (2008) and VetMAX assays, respectively. Using the assays highlighted in our study, pooling at ratios of 1:20 would be technically suitable in BTV-endemic countries for surveillance purposes. As peak viraemia occurs between 7–12 days post infection, a 1:10 pooling ratio is appropriate for post-import testing when animals are sampled within a similar time frame post-import.